(untitled) (Asian Journal of Medical and Biological Research, 2015)
Global climate change has triggered the increased incidence of extreme disasters like cyclone, flood, soil salinity, etc. in the coastal region of Bangladesh. In the recent past, an amplified number of fatalities happened and the greater impact also acted upon the attitude of coastal people. Badarpur Union under Patuakhali Sadar upazila of Patuakhali District was the selected locale of the concerned study. Data for this research work were personally collected from a randomly sampled 121 farmers from different villages of Badarpur union by using an interview schedule. Attitude of the farmers was ascertained through a five-point-Likert type scale. Co-efficient of correlation (r) was computed to explore the relationships between farmers? attitude and their selected characteristics. The findings revealed that 51.2 percent of the farmers had moderately favourable attitude towards climate change effect while 42.1 percent had slightly favourable and 6.6 percent had highly favourable attitude. The correlation test showed that the education, farming experience, farm size, annual income, training received and agricultural knowledge had positive significant relationships with farmers? attitude towards climate change effect on agriculture while the rest of the characteristics had no relationship in the present study. The focus findings of the present study were that, the attitude of the farmers is changing due to changes in the climatic conditions and there was a positive effect of it on agriculture. Asian J. Med. Biol. Res. June 2015, 1(2): 367-379